Changes in Neighborhood Foodscapes From 2003 to 2023 by Area Rurality in the United States. - Wiese, Daniel; Shams-White, Marissa M.; Zheng, Zhiyuan; Henry, Kevin A.; McCullough, Marjorie L.; Islami, Farhad (American Journal of Public Health, 2026)
Objectives. To evaluate the change in the US foodscape from 2003 to 2023 overall and by area rurality, considering various modes of transportation. Methods. We conducted this study using longitudinal data on all licensed food retailers, geocoded to census-tract level, and examined changes in the foodscape by estimating the percentages of tracts defined as food deserts (no grocery stores) and food swamps (mostly restaurants or fast-food locations). Results. We found a considerable increase in the percentage of food swamps and no substantial progress in reducing food deserts. For example, using distance-based foodscape measure (one half of a mile from tract borders), between 2003 and 2023, the percentage of tracts categorized as food swamps increased from 80.2% to 88.5%, while the percentage of food deserts decreased minimally from 6.1% to 5.5%. Across all years, the percentage of food deserts was substantially higher in rural areas, and when people used public transit as a mode of transportation. Conclusions. The findings underscore the need for improving accessibility to healthy foods across the United States, particularly in rural areas. Public Health Implications. Expanding public–private partnerships to establish healthy food retailers in food deserts may improve the foodscape quality. (Am J Public Health. 2026;116(7):1004–1014. https://doi.org/10.2105/AJPH.2026.308495)